Waste management strategies for Software Development companies: An explorative text analysis of business sustainability reports - Sambhanthan, A.; Potdar, Vidyasagar (2016)
© 2016 IEEE.This paper documents waste management strategies used by Indian Software Development firms. Indian software development giants' corporate sustainability reports were subjected to content analysis using Nvivo qualitative analysis tool. The content analysis reveals that there are a number of waste types such as e-waste, waste water, recycling waste, construction waste, hazardous waste, solid waste, organic waste, packaging waste, paper waste, wet waste, plastic waste, food waste, dry waste, consumer waste, biomedical waste and biodegradable waste which are recorded in the sustainability reports of Indian software development firms. The key implications includes the usage of government authorized recyclers and other government supported initiatives to support the e-waste recycling and disposal, due-diligence audit process for e-waste dismantlers and recyclers to verify their HSE legal compliances and government regulations pertaining to e-waste management and other specific guidelines to assist in waste management. The paper highlights a number of key waste management strategies and tactics used by Indian software development firms which could be used by the software development organizations around the world as best practices.